Pemberdayaan masyarakat melalui penataan dan pembinaan organisasi PKK dalam memanfaatkan limbah sawit di Kampung Sialang Palas, Riau - Khairul Anwar; Syafri Harto; Isril Isril; Adiwirman Adiwirman; Wan Asrida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This community service activity aims to increase the knowledge and skills of the PKK organization in managing groups and treating palm and livestock waste. This activity was motivated by the condition of Sialang Palas Village, Siak Regency in 2001 as a fast-growing area in Riau province. This area is one of the main targets of implementing the most intensive and extensive oil palm plantation development policy in Riau. But land use and palm oil waste patterns are not optimal. This condition has implications for community household income patterns. The question arises how can waste be utilized? To answer this question, training and counselling activities are carried out using training methods and counseling on open governance models and Appropriate Technology (TTG). Activities are conducted in groups with leadership, management and technology knowledge of sawot and livestock waste management. The results of the community service activities are: First, the knowledge and skills to manage the group. Second, the skills to process palm oil and cattle waste into plates, mats, briquettes and fertilizers. This waste declining product is expected to be an alternative household income for the community and independent smallholders, especially during the rejuvenation of oil palm (replanting).